(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2017)
The article shows the results of a community study carried out by the Monitoring Centre on Organized Crime of the University of Milan concerning the criminality and the perception of security in Pregnana Milanese, a little town of Milan’s hinterland. Throughout a qualitative approach (field observation, interviews, focus group), along with the analysis of socio-economic and criminal statistical data, the research has reconstructed the socio-demographic, economic, urbanistic fabric of the town, the criminal scenario and the citizens’ perception of security, and finally the responses of the local institutions to the challenges posed by the criminality and the citizens’ requests in terms of security. The results of the analysis highlight the absence of mafia embedment process and attribute the refractoriness to such phenomenon to the effectiveness of local policies, that have allowed the institutions to “occupy” the territory and, therefore, not leave empty spaces that could offer the mafias the opportunity of infiltrating and settlement, as much as it has occurred in some of the near towns. Keywords: Criminality, perception of security, mafia, community, local policies, control, territory